Electrical control system of power plant simulation based on modular analysis. (2018) - Jing, Fan
This paper performs intensive study on the electrical modelling and simulation of power plant and establish corresponding mathematical model. Modular analysis is adopted and the core parts of simulation are provided including generator, excitation system and transformer. For different actual problems and analysis tools the generator model gets simplification and practical models of generator are finally established. Using these algorithms, the logic of functional components and the logic of the subsystem are established, and the model of the entire electrical system can also be constructed. By the system model running on simulators, we use related software to simulate electrical system. The data of system model is stable and vivid by parameter adjustment and optimisation, so our model is proved to be feasible and to provide theoretical reference for electric running and maintenance.